The effect of refrigeration and room temperature storage conditions on the physico-chemical characteristics of hybrid and freeze-dried blueberries - Tamás Antal (Journal of Agriculture and Food Research, 2024)
In order to preserve the nutritional properties of fruits after dehydration, it is necessary to use appropriate storage methods. The traditional freeze-dried and combination-dried i. e. vacuum pre- and freeze post-dried, freeze pre- and vacuum post-dried, mid-infrared-freeze-dried, and freeze-mid-infrared dried blueberry samples were stored in vacuum packs for 6 months. The reference drying method, i.e. freeze drying at a pressure of 80–90 Pa and a temperature range between −25 and 20 °C, with a drying time of 22 h, was used. The blueberries were mid-infrared dried at 60 °C for 5 min before and after freeze-drying, and the experimental materials were also vacuum dried at 60 °C for 4 h at 7 kPa vacuum pressure before and after freeze-drying. Drying operation times were ranked from the shortest to the longest as follows: freeze-mid-infrared drying, mid-infrared freeze-drying, freeze pre- and vacuum post-drying, and vacuum pre- and freeze post-drying and conventional lyophilization. The aim of this study was to investigate the effects of different storage conditions, namely refrigeration (5 °C in a refrigerator) and room temperature (23 °C on a shelf in a dark place) on the moisture content, water activity, firmness, rehydration ratio, polyphenol- and flavonoid content, as well as antioxidant capacity of dried blueberries. The dried and vacuum-packaged blueberries stored in the refrigerator and at room temperature can be characterized by the stability of their physical and chemical properties throughout the storage period. It was found that a traditional freeze-drying (FD), freeze-drying and vacuum-drying combination of 4 h at 60 °C (FD-VD4h60 °C) together with vacuum packaging at ambient temperature, is sufficient to ensure a shelf-stable whole blueberry product.